2x + y = 6; 4 – 3x/4 = y

v. 2x + y = 6;   4 – 3x/4 = y

2x + y = 6

X
0
1
2
Y
6
4
2
(X,Y)
(0,6)
(1,4)
(2,2)

Put, x = 0
2(0) + y = 6
y = 6
Put, x = 1
2(1) + y = 6
2 + y = 6
y = 6 – 2
y = 4
Put, x = 2
2(2) + y = 6
4 + y = 6
y = 6 – 4
y = 2

4 – 3x/4 = y
4 – 3x = 4y
X
0
4
-4
Y
1
-2
4
(X,Y)
(0,1)
(4,-2)
(-4,4)

Put, x = 0
4 – 3(0) = 4y
4 – 0 = 4y
4 = 4y
4/4 = y
1 = y
y = 1
Put, x = 4
4 – 3(4) = 4y
4 – 12 = 4y
- 8 = 4y
-8/4 = y
- 2 = y
y = - 2
Put, x = - 4
4 – 3 ( - 4 ) = 4y
4 + 12 = 4y
16 = 4y
16/4 = y
4 = y
y = 4




 x = 4 and y = – 2 is the solution of given simultaneous equations.

No comments:

Post a Comment